Peripheral vertigo and appropriate use of Betahistine to improve outcomes - Raheja, Girish (International Journal of Research in Medical Sciences, 2024)
Vertigo, characterized by a spinning or whirling sensation, is a common condition with a prevalence of 4.9% in the general population. It is caused by dysfunction in the vestibular system and can be classified as peripheral or central. Common causes of peripheral vertigo include benign paroxysmal positional vertigo (BPPV), Meniere’s disease, and vestibular neuritis. Betahistine hydrochloride, a structural analog of histamine, is a commonly used treatment for peripheral vertigo. It acts as both a histamine H1 antagonist and a partial inverse agonist, improving cochlear blood flow and inhibiting vestibular neuronal firing. Betahistine has been shown to be effective in controlling symptoms, reducing frequency and intensity of vertigo attacks, and improving quality of life.